Lesions of the posterior paraventricular nucleus of the thalamus attenuate fear expression - Li, Yonghui; Dong, Xinwen; Li, Sa; Kirouac, Gilbert J. (Frontiers in Behavioral Neuroscience, 2014)
The paraventricular nucleus of the thalamus (PVT) has generated interest because of its strong projections to areas of the brain associated with the regulation of emotional behaviors. The posterior aspect of the PVT (pPVT) is notable for its projection to the central nucleus of the amygdala which is essential for the expression of a conditioned fear response. The present study was done to determine if the pPVT is involved in the expression of fear by examining the effect of post-conditioning lesions of the pPVT. Male rats were trained to bar press for food pellets on a variable ratio schedule. Fear conditioning was done using auditory tones (30 s) that co-terminate with footschocks (0.65 mA, 1.0 s). Rats were anesthetized 24 hours later and small bilateral electrolytic lesions of the pPVT were made. Fear expression to the tone was assessed using suppression of bar-pressing and freezing after one week of recovery from the surgical procedure. Small bilateral lesions of the pPVT increased bar-pressing for food and decreased freezing during the presentation of the conditioned tone. Lesions of the pPVT had no effect on fear extinction, fear conditioning to a novel tone, or the motivation for food as assessed using a progressive ratio schedule. The results of the experiment support a role for the pPVT in fear expression. In contrast, the pPVT does not appear to be involved in fear learning or extinction nor does it appear to play a role in the motivation of rats to bar press for food.